High-performance analysis of biological systems dynamics with the DiVinE model checker - Barnat, Jirí; Brim, Lubos; Safránek, Dravid (Briefings in bioinformatics, 2010)
The current interest in systems biology is to gain a better understanding of how the complex dynamic behaviour of the cell emerges from mutual interactions of molecular species. When solving such a nontrivial goal, biological data have to be necessarily integrated with mathematical modelling and computer analysis. Since the key aspect of biological modelling is based on unifying several kinds of data captured in terms of large-scale biological networks, scalable and automatized methods are necessary to obtain novel predictions and understanding. In this review, we provide a brief description of the tool DiVinE adapted for automatized analysis of biological systems dynamics. The tool employs high-performance computing techniques to enable analysis of large models.
Keywords: Computer Simulation; Algorithms; Software; Software Design; počítačová simulace; Programming Languages; programovací jazyk; software; systémová integrace; biologické modely; Biology; biologie; Systems Integration; algoritmy; navrhování softwaru; Models, Biological